Membrane Fouling Alleviation by Chemically Enhanced Backwashing in Treating Algae-Containing Surface Water: From Bench-Scale to Full-Scale Application - Xiaobin Tang; Tiecheng Guo; Haiqing Chang; Xiao Yue; Jinlong Wang; Haikuan Yu; Binghan Xie; Xuewu Zhu; Guibai Li; Heng Liang (Engineering, 2022)
Ultrafiltration (UF) has been increasingly implemented in drinking water treatment plants; however, algae and their secretions can cause severe membrane fouling and pose great challenges to UF in practice. In this study, a simple and practical chemically enhanced backwashing (CEB) process was developed to address such issues using various cleaning reagents, including sodium hypochlorite (NaClO), sodium chloride (NaCl), sodium hydroxide (NaOH), sodium citrate, and their combinations. The results indicate that the type of chemical played a fundamental role in alleviating the hydraulically irreversible membrane fouling (HIMF), with NaClO as the best-performing reagent, followed by NaCl. Furthermore, a CEB process using a combination of NaClO with NaCl, NaOH, or sodium citrate delivered little improvement in the alleviation of membrane fouling compared with NaClO alone. The optimized dosage and dosing frequency of NaClO were 10 mg·L−1 two times per day. Long-term pilot-scale and full-scale experiments further verified the feasibility of the CEB process in relieving algae-derived membrane fouling. Compared with the conventional hydraulic backwashing without chemical involvement, the CEB process can effectively remove the organic foulants including biopolymers, humic substances, and protein-like substances by means of oxidization, thereby weakening the cohesive forces between the organic foulants and the membrane surface. Therefore, the CEB process can efficiently alleviate the algae-related membrane fouling with lower chemical consumption, and is proposed as an alternative to control membrane fouling in treating the algae-containing surface water.